Analysing The Influence Of Perceived Scarcity, Negative Feelings, And Status Consumption On Food Waste Among Consumers - Muhamad Azrin Nazri; Azreen Jihan Che Mohd Hashim; Nor Asiah Omar; Suhaily Mohd Ramly; Siti Ngayesah Ab Hamid (Journal of Environmental Treatment Techniques, 2024)
Non-Indexed Publication